Ursolic and Oleanolic Acid in ‘Aroma’ Apple Peel as Affected by Rootstock, Harvest Maturity, and Storage Method - Lv, Yanrong; Tahir, Ibrahim I.; Olsson, Marie E. (HortScience, 2016)
Apples contain substances with health-promoting properties, among them, triterpenes, including oleanolic acid (OA) and ursolic acid (UA), which are thought to have anti-inflammatory activity as well as inhibiting initiation, promotion, and metastasis of cancer. This study evaluated effects of harvest time, rootstock, and storage method on two major triterpenes in apple peel, to enhance the understanding of the relative importance of cultivation and environmental factors influencing triterpene concentration. OA and UA concentrations in the semi-dwarfing ‘MM.106’ rootstock apples were significantly higher than in the dwarfing ‘M.9’ rootstock apples at the majority of harvest times over the 2 years of investigations. In 2012 at harvest time, highest concentrations of OA and UA in ‘MM.106’ rootstock apples were 63.4 and 416.3 μg·cm −2 , respectively, while they were 59.7 and 380.9 μg·cm −2 , respectively, in ‘M.9’ rootstock apples. UA remained fairly stable in most cases during storage, and no difference was found between regular atmosphere storage and controlled atmospheric (CA) storage. OA concentration decreased after harvest time. Furthermore, OA showed different responses to regular atmosphere storage and CA storage, and year-to-year difference was also observed. The two rootstocks showed only slight differences in the effect on total soluble solids (TSS) and fruit color, while the titratable acidity (TA) in apples from trees on ‘M.9’ rootstock had lower levels in most cases at the third harvest time as compared with apples from trees on ‘MM.106’ rootstock. OA concentration was positively correlated with UA concentration both directly at harvest and after storage. OA and UA concentrations were positively correlated with TA and TSS, while they were negatively correlated with red color.